Urban mosque in the compact city of Kuala Lumpur: suitability and design considerations - Asif, Nayeem; Utaberta, Nangkula; Sarram, Arman (CLUJ University Press, 2019)
The government expects the population in Greater Kuala Lumpur will grow up to 10,000,000 by 2020 under the Economic Transformation Programme (ETP). The development of Malaysia is now guided by the national agenda and Vision 2020 that envisions Malaysia as a fully developed country economically, socially, politically and spiritually. Religious facility requirement for Vision 2020 states 309 new mosques have to be established to fulfill the need of the growing population. While the land constraints remain for the city of Kuala Lumpur, the necessity of the ever increasing population cannot be overlooked. This necessitates developing an innovative tool which can provide a layout for maximizing the space use within the limited boundary. This paper studies the current space use patterns and formulates design framework for the mosque as a community center in the urban fabric of Kuala Lumpur. The research method is a combination of a qualitative and quantitative approach. The sample consisted of mosques in Kuala Lumpur, and data collection technique was semi-structured interview and observation. Effective and efficient community development functions are expected from the Institution of the mosque as a community center which can enhance not only to serve and strengthen the relationship of the Muslim community but also strengthen the ties of Malaysia's multiracial society as a whole.